Retention levels and years-after-harvesting influence over soil microbial activity and biomass in Southern Patagonian forests - Toledo, Santiago; Martinez Pastur, Guillermo José; Rodríguez‑Souilla, Julián; Peri, Pablo Luis (MDPI, 2024)
Variable retention harvesting (VRH) was designed for timber purposes and biodiversity conservation in natural forests. This system was globally tested, but few studies are related to soil microbial components. The objective was to evaluate different retention types (aggregated and dispersed retention) considering different years-after-harvesting (6, 9, 16 YAH) on soil microbial community attributes compared with unmanaged primary forests (PF) in Nothofagus pumilio forests of Tierra del Fuego (Argentina). This study also evaluated the influence of climate, soil, and understory vegetation. Results showed that aggregated retention increased microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), and soil basal respiration (SBR) compared to dispersed retention, but with similar values than PF. However, harvested areas decreased MBC/MBN values compared with PF. The results showed an overall decrease in microbial biomass and activity in 9 YAH stands, with a positive recovery at 16 YAH. Soil pH, mean annual temperature, and understory vegetation cover showed a positive relationship with MBC, MBN, and SBR. The recovery after 16 YAH reached to different microbial communities. Therefore, the maintenance of retention components in managed stands for longer periods is needed. The results highlight some advantages of VRH as a tool for conservation of forest-dwelling soil microorganisms, including microbial biomass and activity.